Noise control of a two-stage screw refrigeration compressor. (October 2020) - He, Zhilong; Han, Yaoxiang; Chen, Wenqing; Zhou, Minglong; Xing, Ziwen
Abstract: Twin-screw compressors are widely used in refrigeration systems, but typically suffer from severe vibration and noise due to pulsing gas flow during operation. Gas pulsation is the main noise excitation source of screw compressors, presenting significant fundamental harmonic characteristics. This study examined noise control technologies for screw refrigeration compressor designs, such as acoustic wave interference, gas–solid resonance, and perforated muffler. Based on the structure characteristics and noise spectrum characteristics of a single-machine two-stage screw refrigeration compressor, several noise reduction measures were tested, including a half-wavelength tube, Helmholtz resonator, and multi-cavity series muffler. The experimental results show that after optimization, the noise measured on the exhaust side was reduced from 85.3 dB(A) to 81.9 dB(A) under the rated conditions of −25 °C evaporating temperature and 50 °C condensing temperature. At a constant 50 °C condensation temperature, the noise on the exhaust side of the compressor decreased from 93.7 dB(A) to 85.9 dB(A), an improvement of 7.8 dB(A), at 0 °C evaporation temperature. At an evaporation temperature of 5 °C, the noise on the exhaust side of the compressor decreased from 95.6 dB(A) to 86.5 dB(A), an improvement of 9.1 dB(A), indicating effective optimization under variable working conditions.